Developmental onset of cardiovascular disease—Could the proof be in the placenta?. (23rd January 2019) - D'Errico, Jeanine N.; Stapleton, Phoebe A.
Abstract: The Barker Hypothesis states change to the maternal environment may have significant impacts on fetal development, setting the stage for adult disease to occur. The development of the maternofetal vasculature during implantation and maintenance during pregnancy is extremely precise, yet dynamic. Delays or dysfunction in the orchestration of anatomical remodeling, maintenance of blood pressure, or responsiveness to metabolic demand may have severe consequences to the developing fetus. While these intermissions may not be fatal to the developing fetus, an interruption, reduction, or an inability to meet fetal demand of blood flow during crucial stages of development may predispose young to disease later in life. Maternal inability to meet fetal demand can be attributed to improper placental development and vascular support through morphological change or physiological function will significantly limit nutrient delivery and waste exchange to the developing fetus. Therefore, we present an overview of the uteroplacental vascular network, maternal cardiovascular adaptations that occur during pregnancy, placental blood flow, and common maternal comorbidities and/or exposures that may perturb maternal homeostasis and affect fetal development. Overall, we examine uterine microvasculature pathophysiology contributing to a hostile gestational environment and fetal predisposition to disease as it relates to the Barker Hypothesis .